1978
DOI: 10.1002/ana.410040308
|View full text |Cite
|
Sign up to set email alerts
|

A Behavioral analysis of complete unilateral section of the pyramidal tract at the medullary level in macaca mulatta

Abstract: Ten Macaca mulatta monkeys were operantly conditioned to perform three motor paradigms designed to evaluate single and combination finger movements. Eight of these monkeys were retested after left medullary pyramidotomy; 2 monkeys underwent left medullary pyramidotomy prior to conditioning. All animals were tested for three years after operation. Monkeys with a completely sectioned medullary pyramid could, with time, perform difficult motor paradigms that required: (1) both individual and combination finger mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
28
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(31 citation statements)
references
References 27 publications
3
28
0
Order By: Relevance
“…The pattern of recovery from injury to the brains and spinal cords of nonhuman primates parallels, in some respects, observations in humans: complete or extensive lesions of a system are rarely followed by substantial functional recovery, whereas partial lesions are often accompanied by a substantial degree of functional recovery (Turner, 1891;Mott, 1892;Mettler, 1944;Lassek and Anderson, 1961;Kuypers, 1974;Schwartzman, 1978;Little and Halar, 1985;Roth et al, 1991;Nathan, 1994;Coleman and Geisler, 2004) that is paralleled by systems-level plasticity (Netz and Homberg, 1997;Marshall et al, 2000;Schmidlin et al, 2004). Partial lesions that spare some pathways provide a potential substrate for subsequent spontaneous plasticity in the form of sprouting of spared axons or modified use of spared projections, which could lead to functional improvement.…”
Section: Discussionsupporting
confidence: 58%
“…The pattern of recovery from injury to the brains and spinal cords of nonhuman primates parallels, in some respects, observations in humans: complete or extensive lesions of a system are rarely followed by substantial functional recovery, whereas partial lesions are often accompanied by a substantial degree of functional recovery (Turner, 1891;Mott, 1892;Mettler, 1944;Lassek and Anderson, 1961;Kuypers, 1974;Schwartzman, 1978;Little and Halar, 1985;Roth et al, 1991;Nathan, 1994;Coleman and Geisler, 2004) that is paralleled by systems-level plasticity (Netz and Homberg, 1997;Marshall et al, 2000;Schmidlin et al, 2004). Partial lesions that spare some pathways provide a potential substrate for subsequent spontaneous plasticity in the form of sprouting of spared axons or modified use of spared projections, which could lead to functional improvement.…”
Section: Discussionsupporting
confidence: 58%
“…In the present study, we found that the average firing rate of the units in the thumb abductor muscles, for a contraction of 10-20% MVC, was about 16 Hz over the age range 4-11 years and then decreased with increasing age until the adult value of about 13 Hz was reached. Such a change in motor unit discharge frequency with age would not have contributed to the observed change in motor unit discharge synchrony since the chosen index of synchrony was standardized to a reference discharge frequency of 10 Hz (Harrison et al 1991 (Lawrence & Kuypers, 1968;Passingham, Perry & Wilkinson, 1978;Schwartzman, 1978). In man, following such a lesion, synchrony may be absent (Farmer et al 1993).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, investigations assessed the consequences of pyramidotomy, a lesion aimed at selectively interrupting the CS axons originating from one -or in the case of bilateral pyramidotomy -from both hemispheres (Beck and Chambers 1970;Bucy 1957Bucy , 1966Chapman and Wiesendanger 1982;Hepp-Reymond and Wiesendanger 1972;Hepp-Reymond et al, 1974;Kucera and Wiesendanger 1985;Lawrence and Kuypers 1968;Lawrence and Hopkins 1976;Schwartzmann 1978;Tower 1940;Woolsey et al, 1972). As reviewed in detail (Hepp-Reymond 1982), recovery after pyramidotomy in monkeys is variable and depends upon the precise location and extent of the lesion, post-lesion survival, and evaluation of types of movements and/or behaviour.…”
Section: Introductionmentioning
confidence: 99%